Faktor-Faktor Penyebab Tingginya Beverage Costdi Hotel TSR - Wiryanata, I Gusti Ngurah Agung; Daivi, I Gusti Ayu Agung Satvika (HeadWay Research & Developemnt, 2025)
This study aims to analyze the causes of high beverage costs at TSR Bali hotels. The data analysis technique used is a qualitative descriptive analysis technique. The data collection techniques used are observation, documentation, and interviews. The results of the study found that the standard beverage cost set by the management was 33.00% while the average percentage of actual beverage cost reached 35.02% so that there was a difference of 2.02, the management set a tolerance of 1%. The findings show that the purchase of beverage ingredients is not guided by the standard purchase specification and purchases are not made based on competitive prices. The receiving department in receiving beverage ingredients tends to trust suppliers too much in checking the quality, quantity, and price of beverage ingredients. In the dispensing of beverage materials, there is a lack of precision from the storekeeper when receiving a storeroom requisition that is not equipped with the signature of the head department.